1992
DOI: 10.1016/0882-4010(92)90015-g
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatitis virus A59 increases steady-state levels of MHC mRNAs in primary glial cell cultures and in the murine central nervous system

Abstract: Infection of mixed glial cell cultures with mouse hepatitis virus (MHV)-A59 results in an approximately six-fold increase in the level of major histocompatibility complex (MHC) class I mRNA. In situ hybridization of glial cell cultures infected with MHV-A59 again showed enhanced MHC mRNA expression, both in infected and uninfected cells. These results extend our earlier finding that MHC surface antigens are enhanced on astrocytes and oligodendrocytes after MHV-A59 infection and suggest that this enhancement is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…It has been shown that during an MHV-induced chronic demyelination in the CNS of mice, several inflammatory molecules, such as interleukin 1␤ (IL-1␤), tumor necrosis factor, IL-6, type 2 nitric oxide synthase (53), cytokine response gene 2, RANTES, and macrophage-inflammatory protein 1␤, or their mRNAs are detected (33). Upregulation of MHC class I mRNA and antigen expression has been observed in MHV-infected animals (25,36). The fact that HCoV-OC43 and MHV belong to the same antigenic group (32) is consistent with the possibility that this human virus could act similarly to its murine counterpart in the CNS of its host.…”
Section: Vol 74 2000supporting
confidence: 65%
“…It has been shown that during an MHV-induced chronic demyelination in the CNS of mice, several inflammatory molecules, such as interleukin 1␤ (IL-1␤), tumor necrosis factor, IL-6, type 2 nitric oxide synthase (53), cytokine response gene 2, RANTES, and macrophage-inflammatory protein 1␤, or their mRNAs are detected (33). Upregulation of MHC class I mRNA and antigen expression has been observed in MHV-infected animals (25,36). The fact that HCoV-OC43 and MHV belong to the same antigenic group (32) is consistent with the possibility that this human virus could act similarly to its murine counterpart in the CNS of its host.…”
Section: Vol 74 2000supporting
confidence: 65%
“…Mouse hepatitis virus (MHV) is a neurotropic murine coronavirus that has been used in numerous studies of viral neurovirulence and the mechanism of virus-mediated demyelination in the central nervous system (Fleming et al, 1993;Gilmore et al, 1994;Gombold et al, 1995;Gombold and Weiss, 1992;Hingley et al, 1994;Houtman and Fleming, 1996;Lavi et al, 1984Lavi et al, , 1988Wang et al, 1990;Watanabe et al, 1983;Weiner, 1973). Like all coronaviruses, MHV strain A59 possesses a large (31 kb) single-stranded, positive-sense RNA genome (Lee et al, 1991;Pachuk et al, 1989) that is associated with the viral nucleocapsid protein (Sturman et al, 1980) inside a host cell-derived membrane.…”
Section: Introductionmentioning
confidence: 99%
“…MHV infection of the CNS induces enhanced expression of MHC class I antigens on brain cells in vitro and in vivo [15][16][17][18][19]. However, the significance of MHC induction in mHV infection is still not clear.…”
Section: Introductionmentioning
confidence: 99%